Titanyl phthalocyanines: Electrochemical and spectroelectrochemical characterizations and electrochemical metal ion sensor applications of Langmuir films - Demir, Faruk; Erdogmus, Ali; Koca, Atif (ELSEVIER SCIENCE SA, 2013)
Electrochemical and spectroelectrochemical characterizations of titanyl phthalocyanines, which were peripheral (alpha-TiOPc) and nonperipheral (beta-TiOPc) tetra and octa substituted (octa-TiOPc) with 3,4-(methylendioxy)-phenoxy moieties were performed to determine their possible applications in different electrochemical technologies. Voltammetric and in situ spectroelectrochemical measurements illustrate that position and number of 3,4-(methylendioxy)-phenoxy substituents affect the redox behavior of the complexes. While alpha-TiOPc gives up to four reduction processes, beta-TiOPc and octa-TiOPc gives up to three reduction processes. While octa-TiOPc gives metal-metal-ring-ring reductions, alpha-TiOPc and beta-TiOPc complexes give metal-ring-ring-metal reduction mechanism. Solvent of the media also alter the electrochemical behavior of the complexes. In situ electrocolorimetric measurements shows distinct color differences among the electrogenerated anionic and cationic redox species, which indicates their possible applications in display technologies. Multiple and reversible, diffusion controlled and multi-electron redox reaction indicate possible usage of the complexes especially in electrosensing applications. The complexes sense Ag+ and Pd2+ ions in the solution and in the solid states. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Titanyl; Metallophthalocyanines; Electrochromism; Electrochemistry; Spectroelectrochemistry; Metal ion sensor; GLASSY-CARBON ELECTRODE; ELECTROCATALYTIC PROPERTIES; ELECTRICAL-PROPERTIES; SUBSTITUTED COBALT; THIN-FILMS; COMPLEXES; MANGANESE; TITANYLPHTHALOCYANINES; BEHAVIOR; Chemistry